Biofilm production by uropathogens causing catheter associated urinary tract infection - Tomar, Rashmi; Singh Paviaya, Rajendra; Ghosh, S. J; Murthy, Ramanesh; Pradhan, Sagarika; Agrawal, Ekta (International Journal of Medical Research and Review, 2017)
Background: The microbial populations within urinary catheter frequently develop as bioﬁlms, directly attaching to the surface of catheters. Bacteria in biofilm are protected from antimicrobial chemotherapy as well as host defence mechanisms, establishing chronic persistent infections, septicemia and death if not treated. Material and Method: The present study, includes 200 patients, catheterized for >48 hours at CIMS, Bilaspur. Urine samples were collected and inoculated in nutrient agar, blood agar and MacConkey agar plates and identification done as per standard procedure. This study was conducted to detect biofilm formation ability of uropathogens by two different methods (Tube and Congo red agar method) and compare their antibiotic sensitivity by using Kirby-Bauer disc diffusion method. Results: Out of 200 urine samples significant bacteriuria were detected in 148(74%) of samples and no growth found in 52(26%) samples and 14 samples showed growth of 2 microorganisms. A total no. of 162 microorganisms were isolated from 200 urine samples. Among these 162 isolates E. Coli was 29.62%, Pseudomonas aeruginosa 11.72%, Klebsiella sp 18.51%, Citrobactor sp 7.40%, Staphylococcus aureus 3.08%, and Coagulase negative Staphylococci 11%. Among these 162 isolates, a total of 91(56.17%) isolates showed biofilm production. Percentage of biofilm formation was highest in P. aeruginosa (63.15%). Conclusion: Tube test method was found to be more reliable method. The in vitro antibiotic susceptibility pattern of biofilm producing organisms showed less sensitivity as compared to non-biofilm producing organisms.